Banyu Murti a Musical Creations | Tabuh Kreasi Banyu Murti - Antara, I Kadek Gita Dwi (GHURNITA: Jurnal Seni Karawitan, 2024)
In this independent project program, we want to interpret the changes like the human soul and still adhere to the structure of Karawitan in general, namely by using the Tri Angga concept with Kekebyaran percussion standards, namely Gegineman, Gegenderan, Bapang, and Pengecet. According to the Prakempa book translated by I Made Bandem, this consideration is because nada dung is in the north, and the god is Vishnu. The method used is the method proposed by I Wayan Dibia, namely Panca Sthiti Ngawi Sani. This method combines practical work patterns with theoretical methods. In line with the meaning of the word, which consists of Panca (Kawi language) meaning five, Sthiti (Kawi language) meaning rule, Ngawi (Kawi language) meaning-making or creating, and Sani (Sanskrit language) meaning art, then Panca Sthiti Ngawi Sani contains the meaning of five rules that should be followed in creating works of art. The medium of expression used is the Gong Kebyar gamelan because the stylist wants to make a kekebyar percussion creation that expresses the anger of the soul, which, of course, has a fast and loud tempo, so it is very suitable for the elements in the gong kebyar gamelan.